1989
DOI: 10.1016/0092-8674(89)90630-2
|View full text |Cite
|
Sign up to set email alerts
|

The β-globin dominant control region activates homologous and heterologous promoters in a tissue-specific manner

Abstract: We have introduced a human beta-globin minilocus, containing the recently described dominant control region (DCR), the beta-globin or Thy-1 gene, and a thymidine kinase (tk)-neoR gene into erythroid and non-erythroid cells. Analysis of the transcription levels of the genes shows that the DCR directs high levels of human beta-globin, Thy-1 and tk-neo expression independent of integration sites in an erythroid-specific manner. The presence of the DNAasel hypersensitive sites at the 5' end of the locus is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
157
2
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(166 citation statements)
references
References 38 publications
5
157
2
2
Order By: Relevance
“…Despite the fact that the a-globin gene is transcribed at reasonable rates in many different cell types in tran sient assays, not even low levels of inappropriate celltype expression is seen in transgenic mice carrying the human a-globin gene ; this paper). Thus, it appears that the a-globin gene, itself, is highly tissue specific, because the DCR appears not to suppress transcription in inappropriate tissues (Blom van Assendelft et al 1989;Greaves et al 1989). Therefore, we spec ulate that the a genes may be activated by an, as yet, undefined dominant control region present within the a-globin locus on chromosome 16.…”
Section: Coordinate Regulation Of Human A-and P-globin Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that the a-globin gene is transcribed at reasonable rates in many different cell types in tran sient assays, not even low levels of inappropriate celltype expression is seen in transgenic mice carrying the human a-globin gene ; this paper). Thus, it appears that the a-globin gene, itself, is highly tissue specific, because the DCR appears not to suppress transcription in inappropriate tissues (Blom van Assendelft et al 1989;Greaves et al 1989). Therefore, we spec ulate that the a genes may be activated by an, as yet, undefined dominant control region present within the a-globin locus on chromosome 16.…”
Section: Coordinate Regulation Of Human A-and P-globin Synthesismentioning
confidence: 99%
“…When these sequences are included in a human p-globin construct and are present in transgenic mice or mouse erythroleukemic cells, each copy of the human p-globin gene is expressed as efficiently as the endoge nous mouse p-globin genes (Grosveld et al 1987;Blom van Assendelft et al 1989;Talbot et al 1989). This ex pression is independent of the position of integration of the transgene and exhibits copy-number dependence.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The more recent identification of a dominant control region (DCR} sited at the 5' end of the 13-globin gene cluster Ryan et al 1989b;Talbot et al 1989;Tuan et al 1989;van Assendelft et al 1989) has allowed high levels of human 13-globin expression, equal to those of the endogenous mouse genes, when it is linked to the human gene in MELC stable transfectants {Talbot et al 1989). Although the DCR provides a tissue-specific level of regulation, it is developmental stage independent (Tuan et al 19891, and regulatory sequences closer to the globin genes may be responsible for stage-specific expression (Kollias et al 1986;Chada et al 1987;Trudel et al 1987).…”
mentioning
confidence: 99%
“…Experiments in transgenic mice have shown that human γ and β -globin genes expressed sequentially during development but at a lower level in the absence of LCR [5,6,7]. The linkage of LCR to γ or β -globin gene confers high level expression and position independence on human globin transgene in mice [4,8]. Initially, Behringer et al [5] and Enver et al [7] reported that linkage of γ -globin gene alone to LCR resulted in γ globin gene expression throughout the developmental stages, while linkage of both γ and β -globin genes to LCR conferred a correct stage developmental expression, which led to a proposition that γ to β -globin switching is regulated by reciprocal competition.…”
Section: Introductionmentioning
confidence: 99%